PENGARUH UMUR DAN PENDIDIKAN TERHADAP PENDAPATAN PEKERJA WANITA DI KOTA BONTANG - NOBIYAN SESARIO (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
By the data taken from the labor offices in Bontang City, it was stated that the level of female workers in Bontang City is quite high. This research is done to empirically prove the influence of age and education on the income of female workers in Bontang City. The data processed in this research is entirely primary which is sourced directly from the respondents with questionnaire reference, which then obtained data about level of age, education, and income of the respondents. Analysis is then done by using multiple linear regression techniques with the help of SPSS 21 version software.The result of this research indicates that age has a positive and significantly to the income of female workers, so does education that also has a positive and significant influence but more dominant on the income of female workers.Keyword : Age, Education, Income, and Female Workers.